The association between marijuana and e-cigarette use and exercise behavior among adults - Sophie Boutouis; Frances Wymbs; Berkeley Franz (Preventive Medicine Reports, 2024)
Background: As the prevalence of marijuana and e-cigarette use among American adults rises and the perceived risk decreases, more information is needed on the potential costs and benefits of marijuana and e-cigarette use, including patterns of exercise. Prior studies have found mixed results, lacked data on types of exercise, and involved only adolescents and young adults. Thus, the current study explored whether marijuana and e-cigarette use are associated with strength training, walking for exercise, or general physical activity among adults in the United States. Method: 2,591 adults from Wave V of the National Longitudinal Study of Adolescent to Adult Health (2016–2018) comprised the sample. Separate one-way analyses of variance (ANOVAs) and post hoc tests examined whether participants’ marijuana and e-cigarette use predicted their exercise, while follow-up analyses of covariance (ANCOVAs) probed significant effects. Results: Results indicated that participants’ marijuana and e-cigarette use predicted their walking for exercise, with marijuana users walking the highest number of times per week, followed by non-users, e-cigarette users, and dual users. However, this effect only approached significance after controlling for covariates. There were no significant differences in strength training or general exercise between groups. Conclusion: These findings challenge the stereotype that marijuana and e-cigarette users are less active than non-users, and future research should examine the potential mechanisms of these findings.